2012
DOI: 10.1007/s10886-012-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phenological Stage on Swainsonine and Endophyte Concentrations in Oxytropis sericea

Abstract: Locoweeds are defined as Astragalus and Oxytropis species that cause intoxication due to the alkaloid swainsonine. Swainsonine concentrations in Oxytropis sericea were influenced by location, plant part, and the developmental stage of the plant. Concentrations followed similar trends at each location, generally increasing over the growing season in above-ground parts until the plant reaches maturity with no change in concentration in the crowns. At the onset of senescence, swainsonine decreased in floral parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 27 publications
(43 reference statements)
1
34
0
3
Order By: Relevance
“…Cook et al . () examined the densities of Undifilum endophytes and a trihydroxy indolizidine alkaloid, swainsonine, in several tissues of a locoweed, Oxyropis sericea , and they demonstrated that swainsonine concentration was correlated with endophyte density within individual plant tissues. Although we did not examined the relationship between endophyte and alkaloid densities in each plant tissue, our results indicate that alkaloid accumulation can depend not only on endophyte density but also on plant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cook et al . () examined the densities of Undifilum endophytes and a trihydroxy indolizidine alkaloid, swainsonine, in several tissues of a locoweed, Oxyropis sericea , and they demonstrated that swainsonine concentration was correlated with endophyte density within individual plant tissues. Although we did not examined the relationship between endophyte and alkaloid densities in each plant tissue, our results indicate that alkaloid accumulation can depend not only on endophyte density but also on plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The titre of alkaloids accumulated in a plant usually depends on the titre of endophytes (Cook et al . ). Despite this basic knowledge about endophytes, there are few studies focusing on the relationship between the dynamics of endophytes and the insect resistance of the infected plants in fields.…”
Section: Introductionmentioning
confidence: 97%
“…While the endophyte has been found in all plant parts, it is highest in the crown, and has been difficult to isolate from roots (Cook et al, 2009a;Cook et al, 2011). Endophyte amounts change seasonally in above ground parts of plants until the plants reach maturity (Achata et al, 2012;Cook et al, 2012). Gao et al (2012) cultured Alternaria sect.…”
Section: Introductionmentioning
confidence: 99%
“…Swainsonine (SW) is a toxin produced by locoweeds and harmful to livestock industry [1,2]. Chronic ingestion of SW by livestock can cause many problems, including locoism, birth defects, reproductive disorders, congestive heart failure, edema growth retardation and loss of body condition [3,4,5].…”
Section: Introductionmentioning
confidence: 99%